Positive electrode and power storage element
By optimizing the particle size distribution of the positive electrode active material in all-solid-state secondary batteries, the ionic conductivity and charging capacity are enhanced, addressing the conductivity challenges in existing electrodes.
Patent Information
- Application Number
- JP2023096523
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-06-12
AI Technical Summary
Existing positive electrodes for all-solid-state secondary batteries face challenges in achieving good ionic conductivity, which affects the performance and capacity of the battery.
The positive electrode is designed with a specific particle size distribution of the active material, having multiple peaks in the particle size distribution diagram, with a majority of the active material within the range of 0.2 μm to 10.0 μm, and a ratio of small to large particles optimized to enhance ionic conductivity.
The optimized particle size distribution leads to improved ionic conductivity and larger charging capacity of the positive electrode, enhancing the overall performance of the power storage element.
Smart Images

Figure 2024178034000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode and an energy storage element including the positive electrode. [Background technology]
[0002] Patent Document 1 describes a positive electrode for an all-solid-state secondary battery including a sulfide-based solid electrolyte, the positive electrode for the all-solid-state secondary battery including a first positive electrode active material having an average particle size of 15 to 20 μm, a second positive electrode active material having an average particle size of 2 to 6 μm, and a solid electrolyte, one or more selected from the group consisting of the first positive electrode active material and the second positive electrode active material include a coating film including a lithium ion conductor, the first positive electrode active material and the second positive electrode active material each include a core and a shell, and the shell includes a nickel-based active material including cobalt (Co). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2021-141064 A Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide a positive electrode having good ion conductivity and an electric storage device including the positive electrode. [Means for solving the problem]
[0005] A positive electrode according to one aspect of the present invention includes a positive electrode active material layer including a solid electrolyte and a particulate positive electrode active material, A particle size distribution diagram of the positive electrode active material, in which the horizontal axis is the logarithm of particle size and the vertical axis is the volume ratio, has a plurality of peaks with different peak top heights within a particle size value range of 0.2 μm or more and 10.0 μm or less on the horizontal axis, A first peak having the highest peak top height among the plurality of peaks has a particle size value (L1) corresponding to the peak top (P1) in the range of 3.0 μm or more and 10.0 μm or less, A second peak having the second highest peak top height among the plurality of peaks has a particle size value (L2) corresponding to the peak top (P2) in the range of 0.2 μm or more and less than 1.0 μm, The ratio (Va / Vt) of the total volume (Vt) of the positive electrode active material having a particle diameter of 0.05 μm or more and 20.0 μm or less among the positive electrode active material is 95 vol% or more, The ratio (Vb / Va) of the total volume (Vb) of the positive electrode active material having a particle diameter of 0.05 μm or more and 2.0 μm or less to the total volume (Va) of the positive electrode active material having a particle diameter of 0.05 μm or more and 20.0 μm or less is 15 volume% or less.
[0006] An energy storage device according to another aspect of the present invention includes the above positive electrode. Effect of the Invention
[0007] The positive electrode according to one aspect of the present invention has good ionic conductivity. In the energy storage device according to another aspect of the present invention, the positive electrode has good ion conductivity. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a perspective view of an energy storage element according to the present embodiment. [Diagram 2] FIG. 2 is a perspective view of an electrode assembly accommodated in the energy storage device of FIG. [Diagram 3] FIG. 3 is a schematic cross-sectional view of an electrode body constituting an energy storage element according to this embodiment. [Figure 4] FIG. 4 is a schematic diagram showing an example of the process for producing a positive electrode active material layer. [Diagram 5] FIG. 5 is a schematic diagram showing an example of a process for producing a solid electrolyte layer. [Figure 6]FIG. 6 is a schematic diagram of an electricity storage device including a plurality of electricity storage elements according to this embodiment. [Figure 7] FIG. 7 is a particle size distribution diagram of a specific example of a positive electrode active material. [Figure 8A] FIG. 8A is a schematic cross-sectional view that illustrates a cross-section of the prepared cell for evaluating a positive electrode active material layer. [Figure 8B] FIG. 8B is a schematic cross-sectional view that illustrates a cross section of the produced electricity storage element (all solid-state secondary battery). [Figure 8C] FIG. 8C is a schematic cross-sectional view that illustrates a cross section of the produced electricity storage element (all solid-state secondary battery). [Figure 9] FIG. 9 is a graph showing an example of a Cole-Cole plot obtained by measuring the AC impedance of the positive electrode active material layer evaluation cell. [Figure 10] FIG. 10 is a graph showing the ionic conductivity of each positive electrode active material layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] An overview of the positive electrode 40 and the energy storage device 1 disclosed in this specification will be given.
[0010] (1) A positive electrode 40 according to one aspect of the present invention includes a positive electrode active material layer 42 including a solid electrolyte and a particulate positive electrode active material, A particle size distribution diagram of the positive electrode active material, in which the horizontal axis is the logarithm of particle size and the vertical axis is the volume ratio, has a plurality of peaks with different peak top heights within a particle size value range of 0.2 μm or more and 10.0 μm or less on the horizontal axis, A first peak having the highest peak top height among the plurality of peaks has a particle size value (L1) corresponding to the peak top (P1) in the range of 3.0 μm or more and 10.0 μm or less, A second peak having the second highest peak top height among the plurality of peaks has a particle size value (L2) corresponding to the peak top (P2) in the range of 0.2 μm or more and less than 1.0 μm, The ratio (Va / Vt) of the total volume (Vt) of the positive electrode active material having a particle diameter of 0.05 μm or more and 20.0 μm or less among the positive electrode active material is 95 vol% or more, The ratio (Vb / Va) of the total volume (Vb) of the positive electrode active material having a particle diameter of 0.05 μm or more and 2.0 μm or less to the total volume (Va) of the positive electrode active material having a particle diameter of 0.05 μm or more and 20.0 μm or less is 15 volume% or less.
[0011] The positive electrode 40 described in (1) above can have good ion conductivity.
[0012] (2) In the positive electrode 40 described in (1) above, a ratio (L1 / L2) of the particle size value (L1) corresponding to the peak top (P1) of the first peak to the particle size value (L2) corresponding to the peak top (P2) of the second peak may be 5 or more and 30 or less.
[0013] The positive electrode 40 described in (2) above may have better ion conductivity.
[0014] (3) In the positive electrode 40 according to (1) or (2) above, the solid electrolyte may be in a particulate form, and the average particle size of the solid electrolyte may be 1.0 μm or less.
[0015] The positive electrode 40 described in (3) above may have better ion conductivity.
[0016] (4) An energy storage device 1 according to another aspect of the present invention includes the positive electrode 40 according to any one of (1) to (3) above. In the energy storage device 1 according to (4) above, at least the positive electrode can have good ionic conductivity. Therefore, the energy storage device 1 can have a larger charging capacity.
[0017] The configuration of the positive electrode 40, the configuration of the energy storage element 1, the configuration of the energy storage device 100, and other embodiments according to one embodiment of the present invention will be described in detail. Note that the names of the components (individual components) used in each embodiment may differ from the names of the components (individual components) used in the background art.
[0018] <Configuration of Energy Storage Element> As shown in FIG. 1 to FIG. 3, the energy storage element 1 according to one embodiment of the present invention includes an electrode body 2 having a positive electrode 40, a negative electrode 50, and a solid electrolyte layer 60, and a container 3 that contains the electrode body 2. The energy storage element 1 according to this embodiment does not substantially contain an electrolyte solution, and may be referred to as an "all-solid-state energy storage element" hereinafter. In this embodiment, the electrode body 2 is a laminated electrode body in which the positive electrode 40, the negative electrode 50, and the solid electrolyte layer 60 are laminated. The container 3 contains the electrode body 2 inside so that the electrode body 2 is sandwiched between two sheets of material. In other words, the container 3 is a so-called pouch container having a flat shape. The positive electrode 40 has a positive electrode active material layer 42 containing a solid electrolyte and a positive electrode active material, and the negative electrode 50 has a negative electrode active material layer 52 containing at least a negative electrode active material. The solid electrolyte layer 60 is disposed between the positive electrode 40 and the negative electrode 50, and mainly contains a solid electrolyte. As an example of the all-solid-state electricity storage element, an all-solid-state lithium ion secondary battery (hereinafter, simply referred to as a "secondary battery") will be described.
[0019] 1 to 3, the energy storage element 1 of this embodiment includes a laminated electrode body 2 in which a positive electrode 40 and a negative electrode 50 are laminated with a solid electrolyte layer 60 interposed therebetween, the above-mentioned container 3 that houses the electrode body 2, and two external terminals (a positive electrode terminal 4 and a negative electrode terminal 5). The positive electrode terminal 4 is configured as a tab portion formed by a part of a positive electrode substrate 41 (described later) of the positive electrode 40 extending outward. Similarly, the negative electrode terminal 5 is configured as a tab portion formed by a part of a negative electrode substrate 51 (described later) of the negative electrode 50 extending outward. The energy storage element 1 is configured so that electricity flows between the electrode assembly 2 and an arbitrary external device via a positive electrode terminal 4 and a negative electrode terminal 5 during charging and discharging. In the energy storage element 1 of this embodiment, one electrode assembly 2 is housed in a container 3, and the electrode assembly 2 is configured to undergo a charging and discharging reaction. Moreover, the container 3 is preferably in a state in which a compressive force is applied from the outside to the inside in the thickness direction (the stacking direction of the electrodes in the electrode body 2). This can further reduce the interface resistance between the positive electrode 40 and the negative electrode 50 and the solid electrolyte layer 60. The electrode body 2 housed in the container 3 may be one or more.
[0020] In the electrode body 2, a rectangular sheet-shaped positive electrode 40 and a rectangular sheet-shaped negative electrode 50 are stacked with a solid electrolyte layer 60 interposed therebetween. As shown in FIG. 3, the solid electrolyte layer 60 is arranged so as to electrically insulate the positive electrode 40 and the negative electrode 50. The solid electrolyte layer 60 does not contain either a positive electrode active material or a negative electrode active material. In this embodiment, the electrode body 2 and the container 3 both have a flat shape. The electrode body 2 is arranged in the container 3 so that the stacking direction of the electrodes in the electrode body 2 and the thickness direction of the container 3 are the same direction, and at least a part of the electrode body 2 is in contact with the inner surface of the container 3 directly or via a predetermined member or the like.
[0021] In the electrode body 2 of this embodiment, at least the positive electrode active material layer 42 of the positive electrode 40 contains a solid electrolyte. More specifically, in this embodiment, at least the positive electrode active material layer 42 contains particles of the solid electrolyte.
[0022] (positive electrode) The positive electrode 40 has a positive electrode substrate 41 and a positive electrode active material layer 42 that overlaps the positive electrode substrate 41 directly or via a predetermined layer. In this embodiment, the positive electrode substrate 41 and the positive electrode active material layer 42 overlap directly in the positive electrode 40. In this embodiment, the positive electrode active material layer 42 is overlapped on one surface (one side) of the positive electrode substrate 41. The positive electrode active material layer 42 and the negative electrode active material layer 52 cause a charge / discharge reaction between each other.
[0023] The positive electrode substrate 41 has electrical conductivity. Whether or not the positive electrode substrate 41 has electrical conductivity is determined by a volume resistivity of 10 7The threshold value is Ω·cm. The material of the positive electrode substrate 41 is a metal such as aluminum, titanium, tantalum, stainless steel, or an alloy thereof. Among these, aluminum or an aluminum alloy is preferable from the viewpoints of potential resistance, high conductivity, and cost. The positive electrode substrate 41 may be a foil, a vapor deposition film, or the like, and foil is preferable from the viewpoint of cost. Therefore, aluminum foil or aluminum alloy foil is preferable as the positive electrode substrate 41. Examples of aluminum or an aluminum alloy include A1085, A3003, and the like specified in JIS-H-4000 (2014).
[0024] The average thickness of the positive electrode substrate 41 is preferably 1 μm or more and 50 μm or less, more preferably 30 μm or less, and even more preferably 15 μm or less. By setting the average thickness of the positive electrode substrate 41 within the above range, the strength of the positive electrode substrate 41 can be increased while increasing the energy density per volume of the secondary battery.
[0025] In this embodiment, the positive electrode active material layer 42 includes at least a positive electrode active material and a solid electrolyte (described in detail later). The positive electrode active material layer 42 may include a binder. The positive electrode active material layer 42 may include optional components such as a conductive agent and a thickener, as necessary.
[0026] The positive electrode active material can be appropriately selected from known positive electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the positive electrode active material for a lithium ion secondary battery. Examples of the positive electrode active material include lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel type crystal structure, polyanion compounds, chalcogen compounds, and sulfur. Examples of the lithium transition metal composite oxides having an α-NaFeO2 type crystal structure include Li[Li x Ni (1-x) ]O2(0≦x<0.5), Li[Li x Ni γ Co (1-x-γ) ]O2(0≦x<0.5, 0<γ<1), Li[Li x Co (1-x)]O2(0≦x<0.5), Li[LiNiMn (1-x-γ) ]O2(0≦x<0.5, 0<γ<1), Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O2(0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), Li[Li x Ni γ Co β Al (1-x-γ-β) ]O2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), etc. Lithium transition metal composite oxides with spinel crystal structure include Li x Mn2O4, Li x Ni γ Mn (2-γ) O4, etc. Examples of polyanion compounds include LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. Examples of chalcogen compounds include titanium disulfide, molybdenum disulfide, iron sulfide, cobalt sulfide, copper sulfide, nickel sulfide, copper chevrel, etc. In addition, sulfur, bismuth oxide, bismuth plumbate, copper oxide, vanadium oxide, etc. can also be used as the positive electrode active material. The atoms or polyanions in these materials may be partially substituted with atoms or anion species of other elements. The surfaces of these materials may be coated with other materials. In the positive electrode active material layer 42, one of these materials may be used alone, or two or more of them may be used in combination. It is preferable to select a positive electrode active material that is covered with a coating layer containing a material such as a lithium ion conductive oxide. Examples of lithium ion conductive oxides include LiNbO3, Li2WO4, and Li4Ti5O 12 , Li3PO4, etc. Among these, it is preferable to select LiNbO3. The coating layer may cover the entire surface of the positive electrode active material, or may cover only a part of the surface.
[0027] The positive electrode active material is particulate. The average particle size of the positive electrode active material is preferably, for example, 0.05 μm or more and 20.0 μm or less. When the average particle size of the positive electrode active material is equal to or more than the above lower limit, the positive electrode active material is easily manufactured or handled. When the average particle size of the positive electrode active material is equal to or less than the above upper limit, the electronic conductivity of the positive electrode active material layer 42 is improved. When a composite of the positive electrode active material and another material is used (for example, when the surface of the positive electrode active material is covered with a coating layer), the average particle size of the composite is taken as the average particle size of the positive electrode active material. A method for measuring the average particle size will be described in detail later.
[0028] In order to obtain a powder of the positive electrode active material with a predetermined particle size, a pulverizer, a classifier, etc. are used. Examples of the pulverization method include a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve. When pulverizing, wet pulverization in which water or an organic solvent such as hexane is present can also be used. As a classification method, a sieve, a wind classifier, etc. are used as necessary for both dry and wet methods.
[0029] The content of the positive electrode active material in the positive electrode active material layer 42 is preferably 10% by mass to 95% by mass, more preferably 20% by mass to 90% by mass, and even more preferably 30% by mass to 80% by mass. When the content of the positive electrode active material is within the above range, it is possible to achieve both a high energy density of the positive electrode active material layer 42 and a relatively simple production of the positive electrode active material layer 42.
[0030] The positive electrode active material layer 42 includes a solid electrolyte, which will be described in detail later. The solid electrolyte may be, for example, an amorphous lump or a particulate form having a specific shape. The solid electrolyte is appropriately selected from among the solid electrolytes exemplified in the description of the solid electrolyte layer 60, which will be described in detail later. The solid electrolyte included in the positive electrode active material layer 42 may be the same type as the solid electrolyte included in the solid electrolyte layer 60, or may be a different type. The content of the solid electrolyte in the positive electrode active material layer 42 is preferably 5% by mass or more and 90% by mass or less, more preferably 10% by mass or more and 80% by mass or less, and even more preferably 15% by mass or more and 70% by mass or less. When the content of the solid electrolyte in the positive electrode active material layer 42 is within the above range, the electric storage element can have a relatively large electric capacity. The positive electrode active material layer 42 may include a plurality of different solid electrolytes.
[0031] The solid electrolyte contained in the positive electrode active material layer 42 is preferably in the form of particles. The average particle size of the solid electrolyte may be 5.0 μm or less, or may be 4.0 μm or less. The solid electrolyte has an average particle size of preferably 3.0 μm or less, and more preferably 1.0 μm or less, which can improve the contact between the materials contained in the positive electrode active material layer 42. The solid electrolyte may have an average particle size of 0.1 μm or more. The method for measuring the average particle size of the solid electrolyte will be described in detail later. The material of the solid electrolyte will also be described in detail later.
[0032] The particle size distribution of the particulate positive electrode active material contained in the positive electrode active material layer 42 satisfies the following requirements. Specifically, a particle size distribution diagram of a positive electrode active material, in which the horizontal axis is the logarithm of particle size and the vertical axis is the volume ratio, has multiple peaks with different peak top heights within the particle size value range of 0.2 μm or more and 10.0 μm or less on the horizontal axis. Furthermore, the first peak, which has the highest peak top height among the multiple peaks, has a particle size value (L1) corresponding to the peak top (P1) in the range of 3.0 μm or more and 10.0 μm or less, and the second peak, which has the second highest peak top height among the multiple peaks, has a particle size value (L2) corresponding to the peak top (P2) in the range of 0.2 μm or more and less than 1.0 μm. Furthermore, the proportion (Va / Vt) of the total volume (Vt) of the positive electrode active material having a particle diameter of 0.05 μm or more and 20.0 μm or less is 95 volume% or more, and the proportion (Vb / Va) of the total volume (Vb) of the positive electrode active material having a particle diameter of 0.05 μm or more and 2.0 μm or less is 15 volume% or less of the total volume (Va) of the positive electrode active material having a particle diameter of 0.05 μm or more and 20.0 μm or less.
[0033] In the energy storage element 1 of this embodiment, the particle size distribution diagram of the positive electrode active material contained in the positive electrode active material layer 42 of the positive electrode 40 satisfies the above-mentioned requirement, and therefore the positive electrode 40 has good ionic conductivity. Since the positive electrode 40 has good ionic conductivity, the energy storage element 1 of this embodiment can have a relatively large charging capacity.
[0034] For example, by producing the positive electrode active material layer 42 using a mixed powder obtained by mixing a powder of a positive electrode active material having an average particle size of about 5.0 μm and a powder of a positive electrode active material having an average particle size of about 0.5 μm such that the amount of the former is greater than the latter, the positive electrode active material layer 42 having the above-mentioned configuration can be obtained.
[0035] The ratio (Vb / Va) may be 10% by volume or less, or 5% by volume or less. The ratio (Vb / Va) may be 1% by volume or more. When the ratio (Vb / Va) is within the above range, the ionic conductivity of the positive electrode 40 may be improved.
[0036] The ratio (L1 / L2) of the particle size value (L1) corresponding to the peak top (P1) of the first peak to the particle size value (L2) corresponding to the peak top (P2) of the second peak may be not less than 5 and not more than 30. This allows the energy storage device 1 to have a larger charging capacity. The above ratio (L1 / L2) may be 20 or less.
[0037] Preparation of samples for measurement such as particle size distribution measurement of positive electrode active material and solid electrolyte (including pretreatment method) The particles of the positive electrode active material to be subjected to various measurements (particle size distribution measurement, average particle size measurement, etc.) are prepared as follows. When measuring the particle size distribution of the powdered positive electrode active material before fabricating the positive electrode, the powder of the positive electrode active material is directly subjected to the measurement. Specifically, when measuring the particle size distribution of the positive electrode active material, all the positive electrode active materials for constituting the positive electrode active material layer 42 are mixed, and the particle size distribution of the mixture is measured. On the other hand, when disassembling an electric storage device and measuring the particle size distribution of the positive electrode active material taken out from the positive electrode, the electric storage device (secondary battery, etc.) is put into a discharged state by the procedure described below before disassembling the electric storage device (secondary battery, etc.) In the following, a secondary battery is described in detail, but the same procedure can be used for electric storage devices other than secondary batteries. First, constant current charging is performed at a current of 0.1 CmA until the battery voltage reaches the battery voltage at which charging is terminated during normal use, and then constant voltage charging is performed at the same battery voltage until the current value decreases to 0.01 CmA to obtain a fully charged state. After a 30-minute rest, constant current discharging is performed at a current of 0.1 CmA until the battery voltage reaches the battery voltage at which discharging is terminated during normal use to obtain a fully discharged state. Note that "normal use" refers to the case where the secondary battery is used under the recommended or specified charging and discharging conditions for the secondary battery. If the secondary battery uses a metallic lithium electrode as the negative electrode, the secondary battery is fully discharged, and then the secondary battery is disassembled and the positive electrode is removed. On the other hand, if the secondary battery does not use a metallic lithium electrode as the negative electrode, in order to accurately control the positive electrode potential, it is desirable to disassemble the secondary battery and remove the positive electrode, and then assemble a test battery with a metallic lithium electrode as the counter electrode, and then adjust the battery to a fully discharged state according to the above procedure, and disassemble the test battery and remove the positive electrode. The work from dismantling the secondary battery to removing the positive electrode active material layer is carried out in an argon atmosphere with a dew point of -60°C or less. The positive electrode active material layer is removed from the positive electrode removed by dismantling the secondary battery, and the positive electrode active material contained in the positive electrode active material layer is separated from the solid electrolyte, and the positive electrode active material is collected. For example, the solid electrolyte is appropriately removed by a method such as ultrasonic cleaning using a solvent that dissolves the solid electrolyte, and the positive electrode active material is collected. When the solid electrolyte is a sulfide-based solid electrolyte, examples of the solvent that can dissolve the solid electrolyte include water. When there is no solvent that can dissolve the solid electrolyte, the positive electrode active material can be collected by adopting a precipitation separation method or the like, utilizing the specific gravity difference between the solid electrolyte and the positive electrode active material. If necessary, the following procedure is further carried out. If materials other than the positive electrode active material are still present after removing the solid electrolyte, for example, a process is carried out to burn off the other materials. Specifically, after carrying out a drying process at room temperature for a whole day and night, in order to remove carbonaceous materials that may be used as conductive agents or organic materials that may be used as binders, for example, the material is heated in air at 600°C for 4 hours using a small electric furnace. In this way, the positive electrode active material is collected.
[0038] The solid electrolyte to be subjected to various measurements (particle size distribution measurement, average particle size measurement, etc.) is prepared as follows. When the average particle size and the like of a powdered solid electrolyte are measured before an electricity storage element is produced, the powder of the solid electrolyte is directly subjected to the measurement. On the other hand, when measuring the average particle size of the solid electrolyte contained in the positive electrode active material layer of the positive electrode obtained by dismantling the electric storage device, the positive electrode active material layer taken out by dismantling the electric storage device is dispersed in a solvent in which the solid electrolyte is insoluble, to obtain the solid electrolyte particles. In order to separate the solid electrolyte from materials other than the solid electrolyte, for example, the above-mentioned sedimentation separation method can be adopted. When the solid electrolyte is a sulfide-based solid electrolyte, examples of the solvent insoluble to the solid electrolyte include a mixed solvent of tetralin and anisole, butyl butyrate, ultra-dehydrated heptane, decane, and various other non-polar solvents.
[0039] Measurement of particle size distribution The particle size distribution of the positive electrode active material particles and the particle size distribution of the solid electrolyte particles are each measured by the following method. The measurement device used is a batch-type laser diffraction scattering particle size distribution measurement device (HORIBA, model number: LA-960). The particle size distribution is measured while stirring the dispersion liquid in which the measurement sample is dispersed in the dispersion solvent with a stirrer in a batch-type glass cell. When measuring the particle size distribution of water-soluble solid electrolyte particles, a solvent in which the solid electrolyte is insoluble is used as the dispersion solvent. Also, the measurement is performed with the entire measurement device placed in a dry air atmosphere with a dew point of -40°C or less. Then, using the standard software attached to the measuring device and adopting the standard set conditions (number of plots per order: 17), a particle size distribution diagram is output. Here, the total volume of particles in a given particle size range is calculated from data output using the above-mentioned standard software and adopting standard set conditions.
[0040] -Measuring the average particle size (if required) Based on the particle size distribution measured by the above method while conforming to JIS-Z-8825 (2013) "Particle size analysis - Laser diffraction and scattering method", the value calculated in accordance with JIS-Z-8819-2 (2001) "Expression of particle size measurement results - Part 2: Calculation of average particle size or average particle diameter and moment from particle size distribution" is used as the average particle size, i.e., the value at 50% of the volume-based cumulative distribution (median size).
[0041] Examples of binders that can be included in the positive electrode active material layer 42 of this embodiment include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic, polyimide, etc.; elastomers (rubber-based binders) such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc. In the positive electrode active material layer 42 containing a binder, at least particles (lumps) of the positive electrode active material and the solid electrolyte are bound to each other via the binder.
[0042] When the positive electrode active material layer 42 contains a binder, the content of the binder in the positive electrode active material layer 42 is preferably 0.01 mass % or more and 10 mass % or less, and more preferably 0.1 mass % or more and 7.0 mass % or less. When the content of the binder is within the above range, the positive electrode active material and the solid electrolyte can be stably maintained.
[0043] The conductive agent that may be included in the positive electrode active material layer 42 of this embodiment is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include carbonaceous materials, metals, conductive ceramics, and the like. Examples of carbonaceous materials include graphite, non-graphitic carbon, graphene-based carbon, and the like. Examples of non-graphitic carbon include carbon fiber (e.g., vapor-grown carbon fiber, etc.), pitch-based carbon fiber, carbon black, and the like. Examples of carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, and the like. The conductive agent may be granular or fibrous in shape. One of the conductive agents may be used alone, or two or more may be mixed and used. The above materials may be used in combination. For example, a material in which carbon black and CNT are combined may be used.
[0044] When the positive electrode active material layer 42 contains a conductive agent, the content of the conductive agent in the positive electrode active material layer 42 is preferably 1 mass % or more and 10 mass % or less, and more preferably 3 mass % or more and 9 mass % or less. When the content of the conductive agent is in the above range, the energy density of the secondary battery can be increased.
[0045] When the positive electrode active material layer 42 contains a thickener, examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. When the thickener has a functional group that reacts with lithium or the like, the functional group may be deactivated in advance by methylation or the like.
[0046] (Negative electrode) The negative electrode 50 has a negative electrode substrate 51 and a negative electrode active material layer 52 overlapping the negative electrode substrate 51 directly or via a predetermined layer or the like. In this embodiment, the negative electrode substrate 51 and the negative electrode active material layer 52 overlap directly in the negative electrode 50. In this embodiment, the negative electrode active material layer 52 is overlapped on one surface (one side) of the negative electrode substrate 51.
[0047] The negative electrode substrate 51 is conductive. Metals such as copper, nickel, stainless steel, nickel-plated steel, and aluminum, or alloys thereof are used as the material of the negative electrode substrate 51. Among these, stainless steel, nickel or nickel alloy, or copper or copper alloy are preferable. Examples of the negative electrode substrate 51 include metal foils and vapor deposition films, and metal foils are preferable from the viewpoint of cost. Examples of the negative electrode substrate 51 include stainless steel foils, nickel foils or nickel alloy foils, and copper foils or copper alloy foils. Examples of copper foils include rolled copper foils and electrolytic copper foils.
[0048] The average thickness of the negative electrode substrate 51 is preferably 1 μm or more and 50 μm or less, more preferably 30 μm or less, and even more preferably 15 μm or less. By setting the average thickness of the negative electrode substrate 51 within the above range, it is possible to increase the strength of the negative electrode substrate 51 and to increase the energy density per volume of the secondary battery.
[0049] The negative electrode active material layer 52 contains a negative electrode active material. The negative electrode active material layer 52 may contain a solid electrolyte (described in detail later) and a binder. The negative electrode active material layer 52 may contain optional components such as a conductive agent and a thickener, as necessary. The binder can be selected from the materials exemplified for the positive electrode 40 above. The optional components such as the conductive agent and the thickener can be selected from the materials exemplified for the positive electrode 40 above. In the negative electrode active material layer 52 containing a binder, at least particles (lumps) of the negative electrode active material and the solid electrolyte are bound to each other via the binder.
[0050] The negative electrode active material layer 52 may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I; typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba; and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W, as components other than the negative electrode active material, solid electrolyte, conductive agent, binder, and thickener.
[0051] The negative electrode active material can be appropriately selected from known negative electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the negative electrode active material for lithium ion secondary batteries. Examples of the negative electrode active material include metal Li; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; Li4Ti5O 12 , LiTiO 2、 Examples of the material include titanium-containing oxides such as TiNb2O7, polyphosphate compounds, silicon carbide, and carbon materials such as graphite and non-graphitic carbon (easily graphitized carbon or non-graphitizable carbon). Among these materials, graphite and non-graphitic carbon are preferred. In the negative electrode active material layer, one of these materials may be used alone, or two or more of them may be used in combination.
[0052] "Graphite" refers to graphite that has an average lattice spacing (d 002 ) is 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. Artificial graphite is preferred from the viewpoint of availability of materials with stable physical properties.
[0053] "Non-graphitic carbon" refers to carbon that has an average lattice spacing (d 002 ) is 0.34 nm or more and 0.42 nm or less. Examples of non-graphitizable carbon include non-graphitizable carbon and graphitizable carbon. Examples of non-graphitizable carbon include resin-derived materials, petroleum pitch or petroleum pitch-derived materials, petroleum coke or petroleum coke-derived materials, plant-derived materials, and alcohol-derived materials.
[0054] Here, the "discharged state" of the carbon material means a state in which the carbon material, which is the negative electrode active material, is discharged so that lithium ions that can be absorbed and released during charging and discharging are sufficiently released from the carbon material. For example, in a single-electrode battery using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metallic Li as a counter electrode, the state is one in which the open circuit voltage is 0.7 V or more.
[0055] "Non-graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.36 nm or more and 0.42 nm or less.
[0056] The "graphitizable carbon" is the above d002 This refers to carbon materials with a particle size of 0.34 nm or more and less than 0.36 nm.
[0057] The negative electrode active material is usually a particle (powder). The average particle size of the negative electrode active material can be, for example, 1 nm or more and 100 μm or less. When the negative electrode active material is a carbon material, a titanium-containing oxide, or a polyphosphate compound, the average particle size may be 1 μm or more and 100 μm or less. When the negative electrode active material is Si, Sn, Si oxide, Sn oxide, or the like, the average particle size may be 1 nm or more and 1 μm or less. By setting the average particle size of the negative electrode active material to the above lower limit or more, the negative electrode active material can be easily manufactured or handled. By setting the average particle size of the negative electrode active material to the above upper limit or less, the electronic conductivity of the active material layer is improved. In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, or the like is used. The pulverizing method and the classifying method can be selected from, for example, the methods exemplified for the positive electrode. When the negative electrode active material is a metal such as metallic Li, the negative electrode active material may be in the form of a foil. In this case, the negative electrode active material layer 52 may be made of only the negative electrode active material.
[0058] The content of the negative electrode active material in the negative electrode active material layer 52 is preferably 10% by mass or more and 95% by mass or less, more preferably 20% by mass or more and 90% by mass or less, and further preferably 30% by mass or more and 80% by mass or less. When the content of the negative electrode active material is in the above range, it is possible to achieve both a high energy density of the negative electrode active material layer 52 and a relatively simple production of the negative electrode active material layer 52. When the negative electrode active material is a metal such as metallic Li, the content of the negative electrode active material in the negative electrode active material layer 52 may be 100% by mass.
[0059] The solid electrolyte that can be contained in the negative electrode active material layer 52 can be appropriately selected from the solid electrolytes exemplified in the description of the solid electrolyte layer 60 described later in detail. The solid electrolyte may be, for example, an amorphous lump or a specific shaped particle. The solid electrolyte that can be contained in the negative electrode active material layer 52 may be the same type as the solid electrolyte contained in the solid electrolyte layer 60, or may be a different type. When the negative electrode active material layer 52 contains a solid electrolyte, the content of the solid electrolyte in the negative electrode active material layer 52 is preferably 5 mass% or more and 90 mass% or less, more preferably 10 mass% or more and 80 mass% or less, and further preferably 15 mass% or more and 70 mass% or less. When the content of the solid electrolyte in the negative electrode active material layer 52 is in the above range, the electric storage element can have a relatively large electric capacity. The negative electrode active material layer 52 may contain a plurality of different solid electrolytes.
[0060] In the electrode body 2 of this embodiment, the positive electrode active material layer 42 and the negative electrode active material layer 52 face each other via the solid electrolyte layer 60. When the electrode body 2 is viewed from one side in the stacking direction (thickness direction), the area of the negative electrode active material layer 52 may be larger than the area of the positive electrode active material layer 42. In other words, at least a part of the peripheral portion of the negative electrode active material layer 52 does not have to face the positive electrode active material layer 42 in the thickness direction.
[0061] (solid electrolyte layer) In the electrode body 2 of the present embodiment, a solid electrolyte layer 60 that contains a solid electrolyte but no active material is disposed between the positive electrode 40 and the negative electrode 50. The thickness of the solid electrolyte layer 60 may be 5 μm or more and 200 μm or less, or 10 μm or more and 100 μm or less.
[0062] The solid electrolyte layer 60 contains a solid electrolyte in the form of particles having a specific shape or in the form of chunks having an irregular shape, and may further contain a binder exemplified for the positive electrode 40 above.
[0063] The solid electrolyte is an ion-conductive material that conducts charge-transporting ions such as lithium, sodium, potassium, magnesium, and calcium, and is a compound that maintains a solid state even in a nitrogen atmosphere at 1 atmosphere and 25° C. Examples of the solid electrolyte include sulfide solid electrolytes and solid electrolytes other than sulfide solid electrolytes.
[0064] The solid electrolyte contained in the solid electrolyte layer 60 is preferably a sulfide solid electrolyte. The solid electrolyte contained in the solid electrolyte layer 60 and the solid electrolyte contained in the positive electrode active material layer 42 and the negative electrode active material layer 52 may be the same or different, but preferably, both are sulfide solid electrolytes. The solid electrolyte being a sulfide solid electrolyte has the advantage of being able to increase the conductivity of charge transport ions such as lithium in the solid electrolyte layer. In addition, since the particles of the sulfide solid electrolyte are more easily deformed, the contact area between the particles of the solid electrolyte and between the solid electrolyte and the active material can be made larger. Therefore, there is an advantage that the interface resistance between the solid electrolyte and the active material can be made lower.
[0065] The sulfide solid electrolyte is a compound that contains sulfur element as an essential component and remains solid even under a nitrogen atmosphere at 1 atmosphere and 25°C. When used in a lithium ion secondary battery, examples of the sulfide solid electrolyte include Li2S-P2S5, Li2S-GeS2, LiI-Li2S-P2S5, Li 10 Ge-P2S 12 , Li6PS5X (X=Cl, Br, I), etc. 10 Ge-P2S 12 is called an LGPS-type sulfide solid electrolyte, and Li6PS5X is called an argyrodite-type sulfide solid electrolyte.
[0066] Other solid electrolytes that may be included in the solid electrolyte layer 60 include an oxide solid electrolyte, a nitride solid electrolyte, etc. The solid electrolyte layer 60 may include an inorganic solid electrolyte such as the above-mentioned sulfide solid electrolyte or oxide solid electrolyte, and may further include a polymer solid electrolyte.
[0067] The oxide solid electrolyte is a compound that contains oxygen as an essential component and remains solid even in a nitrogen atmosphere at 1 atmosphere and 25° C. Examples of the oxide solid electrolyte include perovskite-type oxides, NASICON-type oxides, LISICON-type oxides, and garnet-type oxides. Examples of perovskite oxides include Li x La 1-x Examples of such oxides include oxides represented by the formula TiO3 (Li-La-Ti-O perovskite oxides). 0.29 La 0.57 TiO3, Li 0.35 La 0.55 Examples include TiO3. As the NASICON type oxide, for example, Li 1.3 Al 0.3 Ti 1.7 (PO4)3, etc. Examples of LISICON type oxides include Li4SiO4-Li3PO4 and Li3BO3-Li3PO4. Garnet-type oxides include, for example, Li7La3Zr2O 12 and the like Li-La-Zr-O oxides.
[0068] An example of the nitride solid electrolyte is Li3N.
[0069] The polymer solid electrolyte may be an ion-conductive polymer, such as a chemically modified or crosslinked product of a polyether-based, polyester-based, polyamine-based, or polysulfide-based polymer.
[0070] The proportion of the sulfide solid electrolyte in the solid electrolyte contained in the positive electrode active material layer 42, the negative electrode active material layer 52, and the solid electrolyte layer 60 of the electrode body 2 may be 95 mass % or more.
[0071] The solid electrolyte layer 60 may be formed by drying an application of a paste for a solid electrolyte layer that contains a solvent and particles of a solid electrolyte (but does not contain an active material).
[0072] <Method of manufacturing all-solid-state energy storage element> The method for manufacturing the energy storage element of this embodiment includes, for example, a step of producing an electrode body, and a step of housing the electrode body in a container 3 to assemble an energy storage element.
[0073] The process of producing the electrode body includes, for example, preparing a positive electrode mixture paste, a negative electrode mixture paste, and a paste for a solid electrolyte layer, producing a positive electrode active material layer from an application of the positive electrode mixture paste, producing a negative electrode active material layer from an application of the negative electrode mixture paste, and producing a solid electrolyte layer from an application of the paste for a solid electrolyte layer.
[0074] (Preparation of each paste) The positive electrode mixture paste contains at least positive electrode active material particles, solid electrolyte particles, and a solvent, the negative electrode mixture paste contains at least negative electrode active material particles and a solvent, and the solid electrolyte layer paste contains at least solid electrolyte particles and a solvent.
[0075] The solvent is not particularly limited, and may be, for example, an organic solvent or water. As the solvent, for example, a solvent that does not deteriorate the solid electrolyte to be used can be appropriately selected. Since the solid electrolyte may be deteriorated by water, the solvent may be an organic solvent.
[0076] (Preparation of positive electrode active material layer, solid electrolyte layer, and negative electrode active material layer) In the step of producing the positive electrode active material layer, the applied product of the positive electrode mixture paste is subjected to a drying treatment for volatilizing the solvent from the applied product, and is then subjected to a pressing treatment. The negative electrode active material layer (step) and the solid electrolyte layer (step) can be produced in the same manner.
[0077] - Preparation of positive electrode active material layer For example, a metal foil or alloy foil as described above is prepared as the positive electrode substrate 41. As shown in Fig. 4, a positive electrode active material layer 42 can be produced by carrying out the following operations. (I) A positive electrode mixture paste (indicated as PT) is applied to the metal foil or alloy foil of the positive electrode substrate 41. In this way, the applied material is layered on the positive electrode substrate 41. As the application method (coating method), a conventional general method can be adopted. (II) A drying process is performed on the coated product to volatilize the solvent contained in the coated positive electrode mixture paste. For example, the solvent is volatilized and removed from the coated product by a heat treatment. The set temperature during the heat treatment may be, for example, 40° C. or higher and 150° C. or lower. The heat treatment may be performed under reduced pressure. (III) After the solvent has evaporated, the applied material (positive electrode active material layer 42) is subjected to a press treatment (indicated by the dashed arrow). If necessary, the press treatment is performed while heating. (IV) A pressed positive electrode active material layer 42 is formed.
[0078] - Preparation of solid electrolyte layer As shown in FIG. 5, the solid electrolyte layer 60 can be fabricated by carrying out the following operations. (i) A paste for a solid electrolyte layer (denoted as PT') is applied to the positive electrode active material layer 42. In this way, the paste is layered on the positive electrode active material layer 42. As the application method (coating method), a conventional general method can be used. (ii) The applied paste is subjected to a drying treatment for volatilizing the solvent contained in the applied paste for the solid electrolyte layer. For example, the solvent is volatilized and removed from the applied paste by a heat treatment. The set temperature during the heat treatment may be within the temperature range employed for producing the positive electrode active material layer 42, for example. (iii) After the solvent has evaporated, the applied material (solid electrolyte layer 60) is subjected to a pressing process (indicated by the dashed arrow). If necessary, the pressing process is performed while heating. (iv) A pressed solid electrolyte layer 60 is formed.
[0079] - Preparation of negative electrode active material layer Although not shown, the negative electrode active material layer 52 can be produced by a method similar to that used for producing the positive electrode active material layer or the solid electrolyte layer described above.
[0080] In the above, an example has been described in which the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer are produced using the positive electrode mixture paste, the negative electrode mixture paste, and the solid electrolyte layer paste, respectively. However, for example, the positive electrode active material layer may be produced from a positive electrode mixture that does not contain a solvent, the negative electrode active material layer may be produced from a negative electrode mixture that does not contain a solvent, and the solid electrolyte layer may be produced from a powder of a solid electrolyte that does not contain a solvent.
[0081] In the process of producing the electrode body, after producing a laminate of the positive electrode active material layer 42, the solid electrolyte layer 60, and the negative electrode active material layer 52 as described above, the negative electrode substrate 51 is further stacked on top of the laminate and pressed from both sides in the thickness direction, thereby producing the electrode body 2. In the process of preparing the electrode body, the electrode 40 may be prepared by stacking the positive electrode active material layer 42 on the positive electrode substrate 41, and the negative electrode 50 may be stacked on the negative electrode substrate 51 to prepare a laminate of the negative electrode 50 and the solid electrolyte layer 60, and then the laminate and the positive electrode 40 may be stacked and pressed from both sides in the thickness direction to prepare the electrode body 2. In addition, the electrode 40 may be prepared by stacking the positive electrode active material layer 42 on the positive electrode substrate 41, the negative electrode 50 may be stacked on the negative electrode substrate 51 to prepare a negative electrode 50, and the solid electrolyte layer 60 may be stacked and pressed from both sides in the thickness direction to prepare the electrode body 2.
[0082] (Process for assembling the energy storage element) In this step, the produced electrode body 2 is housed in a container 3, and the energy storage element 1 is assembled such that the positive electrode 40 and the negative electrode 50 of the electrode body 2 are electrically connected to the external terminals of the energy storage element 1. A general method can be used to assemble the energy storage element.
[0083] In this manner, the energy storage device 1 of the present embodiment can be manufactured.
[0084] <Configuration of the power storage device> The energy storage element 1 of this embodiment can be mounted as an energy storage device 100 (battery module) constituted by assembling a plurality of energy storage elements 1 in a power source for an automobile such as an electric vehicle (EV), a hybrid vehicle (HEV), or a plug-in hybrid vehicle (PHEV), a power source for electronic devices such as a personal computer or a communication terminal, or a power storage power source, etc. In this case, it is sufficient that the technology of the present invention is applied to at least one of the energy storage elements 1 included in the energy storage device 100. 6 shows an example of an energy storage device 100 in which energy storage units 10, each of which is an assembly of two or more electrically connected energy storage elements 1, are further assembled. The energy storage device 100 may include a bus bar (not shown) that electrically connects two or more energy storage elements 1, a bus bar (not shown) that electrically connects two or more energy storage units 10, etc. The energy storage unit 10 or the energy storage device 100 may include a status monitoring device (not shown) that monitors the status of one or more energy storage elements.
[0085] <Other embodiments> The energy storage element of the present invention is not limited to the above-described embodiment, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and a part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, a part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.
[0086] In the above embodiment, the case has been described in which the energy storage element 1 is used as a chargeable and dischargeable all-solid-state secondary battery (for example, an all-solid-state lithium ion secondary battery), but the type, shape, size, capacity, etc. of the energy storage element are arbitrary.
[0087] In the above embodiment, the positive electrode 40 in which the positive electrode active material layer 42 is superimposed on one side of the positive electrode substrate 41, and the negative electrode 50 in which the negative electrode active material layer 52 is superimposed on one side of the negative electrode substrate 51 have been described. However, in the positive electrode, the positive electrode active material layers may be superimposed on both sides of the positive electrode substrate 41, and in the negative electrode, the negative electrode active material layers may be superimposed on both sides of the negative electrode substrate.
[0088] In the energy storage device 1 of the above embodiment, the positive electrode 40 has good ionic conductivity. Therefore, the energy storage device 1 including such a positive electrode 40 can have a relatively large charge capacity. Specifically, in the particulate positive electrode active material, large particles having a particle size larger than a predetermined value and small particles having a particle size smaller than a specific value are mixed, and the ratio of the small particles is equal to or less than a set value, so that the small particles are arranged in the gaps of the packed structure where the large particles are adjacent to each other, thereby increasing the packing density of the entire positive electrode active material. In addition, a solid electrolyte is present between the large particles and the small particles of the positive electrode active material. As the packing density of the positive electrode active material increases, the width of the ion conduction path formed by the solid electrolyte and the positive electrode active material in the positive electrode active material layer becomes more uniform, and the number of these ion conduction paths also increases. Therefore, the positive electrode 40 has good ion conductivity. As a result, the charging characteristics of the storage element 1 can be improved.
[0089] The energy storage element 1 of the above embodiment is preferably an all-solid-state energy storage element, that is, the positive electrode active material layer 42, the negative electrode active material layer 52, and the solid electrolyte layer 60 of the energy storage element 1 of the above embodiment preferably do not contain an electrolytic solution.
[0090] In the above embodiment, the all-solid-state storage element among the storage elements has been described in detail, but the storage element of the present invention is not limited to the all-solid-state storage element. The positive electrode active material layer, the negative electrode active material layer, and the solid electrolyte layer constituting the storage element of the present invention preferably do not substantially contain an electrolyte solution, but may contain an electrolyte solution. The electrolyte solution can be appropriately selected from known electrolyte solutions. When the storage element of the present invention is a lithium ion secondary battery, for example, the electrolyte solution can be one in which LiPF6 is dissolved as an electrolyte salt in a solvent in which a cyclic carbonate and a chain carbonate are mixed. EXAMPLES
[0091] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0092] Each positive electrode active material layer was prepared as described below, and a positive electrode active material layer evaluation cell including each of the prepared positive electrode active material layers was manufactured. Then, the ionic conductivity of each positive electrode was evaluated.
[0093] (Example 1-1) <Preparation of Positive Electrode Mixture> The following first positive electrode active material and second positive electrode active material were mixed at a volume ratio of 98% (first):2% (second). ·First positive electrode active material (LiNi 0.5 Co 0.2 Mn 0.3 O2, average particle size: 5.0μm) Commercial product ·Second positive electrode active material (LiNi 0.5 Co 0.2 Mn 0.3 O2, average particle size: 0.5μm) Commercially available product The positive electrode active material prepared by the above mixing and an argyrodite-type sulfide solid electrolyte (average particle size: 0.7 μm) were mixed in a volume ratio of 68% (active material):32% (electrolyte) to prepare a positive electrode mixture.
[0094] <Preparation of a cell for evaluating the positive electrode active material layer> A cell for evaluating the positive electrode active material layer was prepared as follows. Specifically, the positive electrode mixture (100 mg) prepared as described above was placed in a stainless steel (SUS) compacted powder molding cell. Next, the positive electrode active material layer was subjected to a pressure of 6 tf / cm 2 The positive electrode active material layer was formed and a cell for evaluating the positive electrode active material layer was fabricated (see FIG. 8A). The electrode area was 1 cm 2 It was.
[0095] (Example 1-2) A cell for evaluating a positive electrode active material layer was produced in the same manner as in Example 1-1, except that the first positive electrode active material and the second positive electrode active material were mixed so that the volume ratio was 96% (first):4% (second).
[0096] (Comparative Example 1-1) A cell for evaluating the positive electrode active material layer was produced in the same manner as in Example 1-1, except that the second positive electrode active material was entirely replaced with the first positive electrode active material, and a positive electrode mixture containing only the first positive electrode active material as the positive electrode active material was prepared.
[0097] (Examples 1-3) A cell for evaluating a positive electrode active material layer was produced in the same manner as in Example 1-1, except that the first positive electrode active material and the second positive electrode active material were mixed so that the volume ratio was 88% (first):12% (second).
[0098] (Examples 1 to 4) A positive electrode active material layer evaluation cell was produced in the same manner as in Example 1-1, except that an argyrodite-type sulfide solid electrolyte having an average particle size of 2.3 μm was used instead of the argyrodite-type sulfide solid electrolyte having an average particle size of 0.7 μm.
[0099] (Comparative Example 1-2) A cell for evaluating a positive electrode active material layer was produced in the same manner as in Example 1-1, except that the first positive electrode active material and the second positive electrode active material were mixed so that the volume ratio was 80% (first):20% (second).
[0100] <Performance evaluation> (Ionic conductivity of positive electrode active material layer) The cells for evaluating the positive electrode active material layer of each of the above-mentioned Examples and Comparative Examples were subjected to AC impedance measurement, and the ionic conductivity of the positive electrode active material layer was calculated from the measurement results. The detailed measurement conditions are as follows. Frequency: 0.01Hz to 7MHz · Amplitude: 10.0mV · Measurement temperature: 25℃ FIG. 9 shows an example of a Cole-Cole plot obtained by measuring the AC impedance of the positive electrode active material layer evaluation cell using each positive electrode active material layer. The values of R1 to R3 obtained from FIG. 9 were substituted into the following formulas, and the ionic conductivity (σ ion ) was sought. The calculation results of the ionic conductivity are shown in Table 1. Moreover, a graph of the calculated ionic conductivity for each of the positive electrode active material layers of the Examples (1-1 to 1-3) and the Comparative Examples (1-1 and 1-2) is shown in FIG.
number
[0101] [Table 1]
[0102] The following procedure was carried out to take out the positive electrode active material from each of the positive electrode active material layer evaluation cells prepared as described above, and to measure the particle size distribution.
[0103] <Particle size distribution of positive electrode active material> (Pretreatment before measurement) The positive electrode active material layer was collected from each of the positive electrode active material evaluation cells prepared as described above, thoroughly washed with water, dispersed in water, and ultrasonically cleaned to remove the solid electrolyte. The layer was filtered, and the filtered material was washed with water and dried overnight at room temperature. Organic matter (e.g., impurities) was then removed by heating at 600°C for 4 hours in an air-flowing atmosphere using a small electric furnace. In this way, particles of the positive electrode active material were collected and used as a sample for measuring the particle size distribution of the positive electrode active material.
[0104] (Particle size distribution measurement) A batch-type laser diffraction scattering particle size distribution measuring device (HORIBA, model number: LA-960) was used as the measuring device. A dispersion liquid was prepared by dispersing the measurement sample collected as described above in water as a dispersion medium. Measurements were performed while stirring the dispersion liquid with a stirrer in a batch-type glass cell. A particle size distribution diagram was output using the standard settings (number of plots per order: 17) in the standard software attached to the measuring device. An example of the particle size distribution diagram of the positive electrode active material of Example 1-1 is shown in FIG. 7.
[0105] From the particle size distribution diagrams of the positive electrode active materials of the obtained examples and comparative examples, the particle size value L1 corresponding to the highest peak top P1 of the first peak and the particle size value L2 corresponding to the second highest peak top P2 of the second peak were obtained within the particle size value range of 0.2 μm to 10.0 μm. In addition, the ratio (Vb / Va) of the total volume (Vb) of the positive electrode active materials having a particle diameter of 0.05 μm to 2.0 μm to the total volume (Va) of the positive electrode active materials having a particle diameter of 0.05 μm to 20.0 μm was calculated. The results are shown in Table 1. In addition, in all the above examples and comparative examples, the ratio (Va / Vt) of the total volume (Vt) of the positive electrode active materials having a particle diameter of 0.05 μm to 20.0 μm was 95 vol% or more. The same was true in the following examples and comparative examples.
[0106] <Average particle size of solid electrolyte> (Pretreatment before measurement) In an argon atmosphere with a dew point of -60°C or less, a positive electrode active material layer was collected from each of the positive electrode active material evaluation cells prepared as described above. The positive electrode active material layer was thoroughly washed with a mixed solvent of tetralin and anisole. The washed solid was left at room temperature in the same atmosphere for a day and night. Thereafter, using a small electric furnace installed in the same atmosphere, the solid was heat-treated at 600°C for 4 hours under argon gas flow with a dew point of -60°C or less to remove organic matter (e.g., impurities, etc.). Next, the solid was dispersed in a mixed solvent of the same composition as above, and solid electrolyte particles were separated by a precipitation separation method using specific gravity difference, and this was used as a sample for measuring the particle size distribution of the solid electrolyte.
[0107] (Average particle size based on particle size distribution measurement) A batch-type laser diffraction scattering particle size distribution analyzer (HORIBA, model number: LA-960) installed in an argon atmosphere with a dew point of -60°C or less was used as the measuring device. A dispersion liquid was prepared by dispersing the measurement sample collected as described above in a mixed solvent of the same composition as above as a dispersion medium. The measurement was performed while stirring the dispersion liquid with a stirrer in a batch-type glass cell. A particle size distribution diagram was output using the standard conditions (number of plots per order: 17) set in the standard software attached to the measuring device. Based on the particle size distribution measured by the above method in accordance with JIS-Z-8825 (2013), the value (median diameter) at which the volume-based cumulative distribution is 50% calculated in accordance with JIS-Z-8819-2 (2001) was adopted as the average particle size. The results are also shown in Table 1.
[0108] Next, each positive electrode was prepared as described below, and an electricity storage element (all solid-state secondary battery) including each of the prepared positive electrodes was manufactured. Then, the charge capacity of each electricity storage element (all solid-state secondary battery) was evaluated.
[0109] (Example 2-1) <Preparation of Positive Electrode Mixture> The following first positive electrode active material and second positive electrode active material were mixed at a volume ratio of 98% (first):2% (second). ·First positive electrode active material (LiNi 0.5 Co 0.2 Mn 0.3 O2, average particle size: 5.0μm) Commercial product ·Second positive electrode active material (LiNi 0.5 Co 0.2 Mn 0.3 O2, average particle size: 0.5μm) Commercially available product The positive electrode active material prepared by the above mixing and an argyrodite-type sulfide solid electrolyte (average particle size: 0.7 μm) were mixed in a volume ratio of 68% (active material):32% (electrolyte) to prepare a positive electrode mixture.
[0110] <Manufacture of positive electrodes and storage elements (all-solid-state secondary batteries)> In order to measure the charge capacity, an electricity storage element (all-solid-state secondary battery) was produced as follows. In detail, first, the powder (100 mg) of the argyrodite-type sulfide solid electrolyte was placed in a pressed powder molded cell made of SUS. 2 A powder compaction process was carried out at a pressure of 6 tf / cm to form a solid electrolyte layer (separator). Next, the positive electrode mixture (20 mg) prepared as described above was placed on the solid electrolyte layer (separator) in the powder compaction cell. Then, a pressure of 6 tf / cm was applied to the positive electrode mixture and the solid electrolyte layer (separator). 2 The positive electrode active material layer was formed by carrying out a powder compaction process and a bonding process at a pressure of 1 tf / cm. Then, a counter electrode made of an In-Li alloy was placed on the side of the solid electrolyte layer (separator) to which the positive electrode active material layer was not bonded. Then, the positive electrode mixture, the solid electrolyte layer (separator), and the counter electrode were subjected to a pressure of 1 tf / cm. 2 The bonding process was carried out at a pressure of 1000 MPa to produce an energy storage element (all-solid-state secondary battery) (see FIG. 8B). The electrode area was 1 cm 2 It was.
[0111] (Example 2-2) An energy storage element (all-solid-state secondary battery) was produced in the same manner as in Example 2-1, except that the first positive electrode active material and the second positive electrode active material were mixed so that the volume ratio was 96% (first):4% (second).
[0112] (Example 2-3) An energy storage element (all-solid-state secondary battery) was produced in the same manner as in Example 2-1, except that the first positive electrode active material and the second positive electrode active material were mixed so that the volume ratio was 88% (first):12% (second).
[0113] (Comparative Example 2-1) An energy storage element (all-solid-state secondary battery) was produced in the same manner as in Example 2-1, except that the first positive electrode active material and the second positive electrode active material were mixed so that the volume ratio was 80% (first):20% (second).
[0114] (Comparative Example 2-2) An electricity storage element (all solid-state secondary battery) was produced in the same manner as in Example 2-1, except that a second positive electrode active material having an average particle size of 0.15 μm was used instead of the second positive electrode active material having an average particle size of 0.5 μm.
[0115] <Performance evaluation> (Charging capacity) The charge capacity of each storage element (all-solid-state secondary battery) was measured by the following charge / discharge test. Details of the test method for the charge / discharge test are as follows. ·Charging conditions: 0.1, 0.2, 0.5, 1, 2 C constant current charging (1C:2.83 mAh / cm 2 ) Charging cut-off voltage: 4.4 V vs. Li + / Li Discharge conditions: 0.1C constant current, constant voltage discharge Discharge cut-off voltage: 3.0 V vs. Li + / Li ·Measurement temperature: 25℃ The measured values of the 0.1 C charge capacity and the 2 C charge capacity were divided by the mass of the positive electrode active material to obtain the 0.1 C charge capacity and the 2 C charge capacity. The results are shown in Table 2.
[0116] [Table 2]
[0117] Furthermore, each positive electrode was prepared as described below, and an electricity storage element (all-solid-state secondary battery) including each of the prepared positive electrodes was manufactured. Then, the charge capacity of each electricity storage element (all-solid-state secondary battery) was evaluated.
[0118] (Example 3-1) <Preparation of Positive Electrode Mixture Slurry> The following first positive electrode active material and second positive electrode active material were mixed at a volume ratio of 98% (first):2% (second). ·First positive electrode active material (LiNi 0.5 Co 0.2 Mn 0.3 O2, average particle size: 5.0μm) Commercial product ·Second positive electrode active material (LiNi 0.5 Co 0.2 Mn 0.3 O2, average particle size: 0.5μm) Commercially available product The positive electrode active material prepared by the above mixing, an argyrodite-type sulfide solid electrolyte (average particle size: 0.7 μm), a conductive agent (vapor-grown carbon fiber), and a rubber-based binder were mixed in a volume ratio of 65% (active material): 30% (electrolyte): 2% (conductive agent): 3% (binder), and a tetralin / anisole mixed solvent was further added as a solvent to prepare a positive electrode mixture slurry.
[0119] <Manufacture of positive electrodes and storage elements (all-solid-state secondary batteries)> The positive electrode mixture slurry prepared as above was applied onto an Al current collector foil using a tabletop applicator, and then dried to prepare a sheet-type positive electrode. After pressing the prepared positive electrode, 2 In order to measure the charging capacity, an electricity storage element (all solid-state secondary battery) was produced as follows. In detail, first, the powder (100 mg) of the argyrodite-type sulfide solid electrolyte was placed in a pressed powder molded cell made of SUS. 2A solid electrolyte layer (separator) was formed by carrying out a powder compaction process at a pressure of 6 tf / cm. Next, the sheet-type positive electrode prepared as described above was placed on the solid electrolyte layer (separator) in the powder compaction cell. Next, a pressure of 6 tf / cm was applied to the positive electrode and the solid electrolyte layer (separator). 2 The bonding process was carried out at a pressure of 1 tf / cm. Then, an In-Li alloy counter electrode was placed on the side of the solid electrolyte layer (separator) to which the positive electrode was not bonded. Then, a pressure of 1 tf / cm was applied to the positive electrode, the solid electrolyte layer (separator) and the counter electrode. 2 The bonding process was carried out at a pressure of 1000 MPa to produce an energy storage element (all-solid-state secondary battery) (see FIG. 8C). The electrode area was 1 cm 2 It was.
[0120] (Comparative Example 3-1) An energy storage element (all-solid-state secondary battery) was manufactured in the same manner as in Example 3-1, except that the second positive electrode active material was entirely replaced with the first positive electrode active material, and a positive electrode mixture slurry containing only the first positive electrode active material as the positive electrode active material was prepared.
[0121] <Performance evaluation> (Charging capacity) The charge capacity of each storage element (all-solid-state secondary battery) was measured by the following charge / discharge test. Details of the test method for the charge / discharge test are as follows. ·Charging conditions: 0.1, 0.2, 0.5, 1, 2, 3 C constant current charging (1C:2.83 mAh / cm 2 ) Charging cut-off voltage: 4.4 V vs. Li + / Li Discharge conditions: 0.1C constant current, constant voltage discharge Discharge cut-off voltage: 3.0 V vs. Li + / Li ·Measurement temperature: 25℃ The measured values of the 0.1C charge capacity, the 2C charge capacity, and the 3C charge capacity were divided by the mass of the positive electrode active material to obtain the 0.1C charge capacity and the 2C charge capacity. The results are shown in Table 3.
[0122] [Table 3]
[0123] As can be seen from Table 1, the positive electrodes of Examples 1-1 and 1-2 had good ionic conductivity in the positive electrode active material layer, whereas the positive electrodes of Comparative Examples 1-1 to 1-3 had poor ionic conductivity in the positive electrode active material layer. As can be seen from Table 2, the energy storage elements of Examples 2-1 and 2-2 had larger charge capacities than the energy storage elements of Comparative Examples 2-2 to 2-4. As can be seen from Table 3, the energy storage element of Example 3-1 had larger charge capacity than the energy storage element of Comparative Example 3-1. [Explanation of symbols]
[0124] 1: Energy storage element (all-solid-state secondary battery), 2: Electrode body, 3: Container, 4: positive terminal, 5: negative terminal, 40: Positive electrode, 41: positive electrode base material, 42: positive electrode active material layer, 50: negative electrode, 51: negative electrode base material, 52: negative electrode active material layer, 60: solid electrolyte layer, 10: power storage unit, 100: power storage device.
Claims
1. A positive electrode active material layer including a solid electrolyte and a particulate positive electrode active material, A particle size distribution diagram of the positive electrode active material, in which the horizontal axis is the logarithm of particle size and the vertical axis is the volume ratio, has a plurality of peaks with different peak top heights within a particle size value range of 0.2 μm or more and 10.0 μm or less on the horizontal axis, A first peak having the highest peak top height among the plurality of peaks has a particle size value (L1) corresponding to the peak top (P1) in the range of 3.0 μm or more and 10.0 μm or less, A second peak having the second highest peak top height among the plurality of peaks has a particle size value (L2) corresponding to the peak top (P2) in the range of 0.2 μm or more and less than 1.0 μm, the ratio (Va / Vt) of the total volume (Vt) of the positive electrode active material having a particle diameter of 0.05 μm or more and 20.0 μm or less among the positive electrode active material is 95 vol% or more; Among the positive electrode active materials, a ratio (Vb / Va) of a total volume (Vb) of the positive electrode active materials having a particle diameter of 0.05 μm or more and 2.0 μm or less to a total volume (Va) of the positive electrode active materials having a particle diameter of 0.05 μm or more and 20.0 μm or less is 15 vol% or less. Positive electrode.
2. 2. The positive electrode according to claim 1, wherein a ratio (L1 / L2) of a particle size value (L1) corresponding to a peak top (P1) of the first peak to a particle size value (L2) corresponding to a peak top (P2) of the second peak is 5 or more and 30 or less.
3. 3. The positive electrode according to claim 1, wherein the solid electrolyte is in a particulate form, and the average particle size of the solid electrolyte is 1.0 μm or less.
4. An energy storage element comprising the positive electrode according to claim 1 or 2.
Citation Information
Patent Citations
Electrode, method of producing the same, battery, and electronic device
JP2016066584A
Positive electrode for all-solid secondary battery, and all-solid secondary battery including the same
JP2021141064A
Positive electrode for solid secondary battery, and solid secondary battery
JP2023100298A
All solid-state lithium-ion cathode
US20220037649A1
Electrode material and battery
WO2022259611A1
